Sandwich nanoarchitecture of LiV3O8/graphene multilayer nanomembranes via layer-by-layer self-assembly for long-cycle-life lithium-ion battery cathodes1. Issue 26 (14th July 2015) - Mo, Runwei; Zhang, Fuwei; Du, Ying; Lei, Zhengyu; Rooney, David; Sun, Kening
<x xml:space="preserve">Abstract</x> Sandwich nanoarchitecture of LiV3O8/graphene multilayer nanomembranes via layer-by-layer self-assembly for long-cycle-life lithium-ion battery cathodes.